Doing Things With Natures: A Performative History in Four Anthropo(s)cenes - Paavolainen, Teemu (Nordic Theatre Studies, 2020)
The article expands on Lewis and Maslin’s “double two-step” historicization of the Anthropocene, with two major transitions in energy (agriculture and fossil fuels) and two in social organization (modernity and the Great Acceleration). Insofar as planetary impacts arise from “what we spend our time doing” – foraging, farming, feudal then waged labour, finally unsustainable consumption – such “doing” is understood as precisely ‘performative’ in the sense that its effects only arise from a massive social repetition that is confused with essential nature and thus concealed. Through a graphic model of such ‘plural performativity,’ four consecutive Anthropo(s)cenes are sketched: the Giving World of agriculture and state formation; the New World of colonial pillage and world trade; the Netherworld of wage labour and fossil capital; then ‘All the World’ but not with all of “us” as players. Apart from environmental changes, the paper targets performances of power and inequality: normative histories of ‘common sense’ on the one hand, concealing ‘people’s histories’ of conflict and opposition, on the other – the Anthropocene arising not simply from what the majority of people have been doing, but from what they have always been forced to do.